Analysis of required investment and benefits using RFID in supply chains - Atanasković Predrag (Industrija, 2012)
Strengthening competition, short product life cycles and technological development of information technology (IT) has changed the ways companies operate. Radio frequency identification technology (RFID) is one of the technologies whose use is being rapidly tested in many fields. At the beginning of this century, the leading retail companies, in cooperation with their suppliers, began the testing of RFID systems application in supply chains. An important component of these studies, besides the effects achieved in the supply chains, is determining the required investments. The approach for the feasibility assessment of investments in RFID systems from the aspect of logistics is presented in this paper, and the results obtained for a realistic two-stage supply chain are given as an example.